Dragon fruit intervention for increasing hemoglobin level on pregnant woment in Sumber Agung Village - Qurniasih, Nila; Besmaya, Beniqna Maharani; Komalasari, Komalasari; Candrasari, Kirana; Primadevi, Inggit (Institute of Computer Science (IOCS), 2024)
Background: Iron Deficiency Anemia is a condition the hemoglobin level less of 11gr%. The global pravalence of anemia in pregnancy is estimated to be approximattely 41,8%. In Indonesia the pravalences anemia reach of 48,9%, and 84,6% beetween occurs in the 15-24 year age group, and in the sumber agung village the number of anemia in 2023 reach of 4 cases. Anemia Assosiated with risk of low birth weight, preterm labor, abortus, postpartum haemorrage and Fetal maternal neonatal death. The Purpose of study is to investigated of Dragon fruit juice within increased level of the hemoglobin in woman’s pregnant in the working area at Sumber Agung Village. Method’s: The study design use quantitative observasional research design, involved 14 participant woman anemia in pregnant, in the each of them comsumed ferosus sulfate and Dragon fruit. The data analyse by descriptive level of hemoglobin before and after intervention. The result showed the mean of level of hemoglobin in woman anemia increased up to 1,4 gr/dl, within seven days intervention. The Conclussion The combination of ferosus sulfate and dragon fruit, describe for increasing level of hemoglobin at woman anemia in pregnancies. Suggestion: Dragon fruid could be an alternative intervention to prevent of anemia in pregnancies.